Strategic Cost Optimization for Efficient Crew Management in Maritime Shipping Operations - Markus Asta Patma Nugraha; Elfira Wirza; Ardiyansyah Widi Prayoga (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rising manning cost over the past three years has become a prominent issue at PT Pertamina International Shipping, where this expense accounts for the largest share of the company’s operational expenditure. This study examines the key factors driving the increase in manning cost and explores how cost efficiency strategies can be applied within the crewing function. Employing a qualitative approach, data were collected through observations, semi-structured interviews with three key personnel, and analysis of financial reports and crew service records over an 11-month period in 2022–2023. The findings reveal three primary inefficiencies scheduling discrepancies causing 2–7 days of delays, suboptimal invoice verification leading to monthly overpayments of approximately 50–100 million rupiah, and overstaffing beyond minimum crew requirements, inflating costs by 10–15%. These inefficiencies result in avoidable expenses of 1–1.5 billion rupiah monthly. The study recommends adopting digital scheduling tools, automated verification systems, and optimized crew allocation to reduce costs while maintaining operational safety. These strategies can save billions annually, improve crew welfare, and contribute to maritime management literature by addressing cost efficiency in state-owned enterprises, offering a blueprint for Indonesia’s shipping industry.